PATHOMORPHOLOGY OF ADRENAL LESIONS IN CORONAVIRUS INFECTION - Najmiddinova Nilufar Nurali Kizi (Western European Studies, 2025)
COVID-19 has been shown to affect numerous organ systems, including the adrenal glands, which play a central role in the body’s stress response. Clinical reports describing earlyonset hypocorticism and acute adrenal insufficiency following SARS-CoV-2 infection suggest that the adrenal glands may be compromised either directly by the virus or indirectly through systemic disease mechanisms. The purpose of this review is to summarize and evaluate current evidence regarding structural, functional, and pathophysiological alterations of the adrenal glands associated with COVID-19. Autopsy findings consistently demonstrate vascular abnormalities—including thrombosis, infarction, hemorrhage, and severe endothelitis—represent another recurrent pattern and highlight substantial microcirculatory disruption. Additional findings such as cellular hyperplasia, necrosis, lipid degeneration, and focal adrenalitis further support the notion of notable adrenal involvement. Although expression of ACE2, TMPRSS2,and other viral entry– associated proteins in adrenal tissue provides biological probability for SARS-CoV-2 infection of adrenal cells, the limited number of virus-positive cells observed suggests that direct cytopathic injury is unlikely to be the primary mechanism. Collectively, the available literature underscores the multifactorial nature of adrenal involvement in COVID-19 and highlights the necessity for further research to better define the prevalence, underlying mechanisms, and long-term consequences of adrenal dysfunction in affected patients
Keywords: COVID-19; adrenal glands; endocrine glands